A comparison of dietary intake between personnel of a gas processing company and a sample population of public employees from Mashhad. (August 2020) - Ardabili, Hossein Mohaddes; Sheikh Andalibi, Mohammad Sobhan; Safari, Mina; Khakpour, Samaneh; Tayefi, Maryam; Moallem, Seyed Reza; Fayaz, Mojtaba; Zarifian, Ahmadreza; Saberi-Karimian, Maryam; Khorasanchi, Zahra; Pasdar, Alireza; Ferns, Gordon A.; et al.
Summary: Introduction: An imbalanced dietary pattern may result in a number of non-communicable disorders that include: obesity, diabetes, metabolic syndrome, cardiovascular diseases, and subsequently impaired quality of life (QOL). Micro- and macro-nutrients play some important roles in maintaining human health. The objective of this study was to compare dietary intake of employees of a gas processing company, who were provided with meals by their employee, with staff from other public employers from Mashhad, in northeastern Iran. Methods: Twenty-four-hour food recall and a food frequency questionnaire (FFQ) were used to evaluate dietary intakes of 654 male employees of Shahid Hasheminejad Gas Processing (SHGP) Company (case group), and 681 randomly selected male public employees from Mashhad as control subjects in this observational, analytic, longitudinal, prospective cohort study. The analysis of the dietary intakes was performed using Dietplan6 software. Results: Dietary macro and micro-nutrients were evaluated: including total energy, fat, MUFA, PUFA, trans fatty acids, cholesterol, starch, fiber, protein, total nitrogen, zinc, phosphor, potassium, calcium, manganese, selenium, iodine, sodium, copper, retinol, carotene, thiamin, riboflavin, niacin, pantothen, vitamin B6, biotin, folate, vitamin B12, vitamin C and vitamin D. The intake of macro-nutrients, including: energy, fat, monounsaturated fatty acids, polyunsaturated fatty acids, carbohydrates, starch, and protein; minerals including zinc, iron, selenium; and vitamins including niacin and vitamin D were higher in the SHGP group, compared to the control group (P < 0.05). The dietary intake of the SHGP group contained lower amounts of several mineral and vitamins, which included: iodine, sodium, carotene, thiamin, pantothenic acid, vitamin B6, biotin, folic acid, and vitamin C, in comparison with the control group (P < 0.05). Conclusion: In conclusion, we suggest it will be important to evaluate the composition of meals provided by companies and organizations, especially those that provide their employees with the majority of their food intake.